ANALISIS TINGKAT KESEHATAN BANK UMUM BUMN KONVENSIONAL DAN BANK UMUM BUMN SYARIAH - Amelia Rahmi (Universitas Pakuan, 2020)
The purpose of this study is to determine the soundness of sharia BUMN Bank and conventional BUMN bank if measured by RGEC method in 2014-2018. This research is a comparative study that is a study that is comparing, the variable is the same as the independent variable, but for samples that are more than one, or in a time frame different. The population of this study is the Conventional BUMN Bank and Islamic BUMN Bank with period observations between 2014 and 2018. While the sample in this study taken by using a purposive sampling technique. The results showed that the risk of conventional commercial bank loans with Islamic commercial banks there are differences. That commercial bank GCG conventional with Islamic commercial banks there are differences. That conventional commercial bank earnings with Islamic banks there are differences. That conventional commercial bank capital with banks general sharia there are differences. This means that the soundness of conventional commercial banks and banks general sharia based on RGEC there are differences.